Novel reconstruction method by mega-prosthesis wrapped with vancomycin-containing cement after resection of malignancies. Issue 48 (2nd December 2022) - Hashimoto, Kazuhiko; Nishimura, Shunji; Shinyashiki, Yu; Ito, Tomohiko; Kakinoki, Ryosuke; Akagi, Masao
Abstract : To introduce wrapping vancomycin-containing cement around a mega-prosthesis (MP) as a novel method to prevent prosthetic joint infection after reconstruction surgery for malignant bone and soft tissue tumors. Five patients with malignant bone and soft tissue tumors treated at our hospital from April 2009 to December 2019 were included. The average age was 71.4 years. Four males and one female were included. Three patients had a bone tumor, and two had a soft tissue tumor. Three right thighs and two left femurs were affected. These tumors were identified histologically as undifferentiated pleomorphic sarcoma, spindle cell sarcoma, diffuse large cell B-cell lymphoma, metastasis of renal cancer, and metastasis of lung cancer. All patients underwent tumor resection and reconstruction with a MP. In all cases, vancomycin-containing cement (2 g/40 g) was wrapped around the implant at the extension. The average follow-up period was 30.4 months. We surveyed whether infection occurred after surgical treatment. We also investigated the Musculoskeletal Tumor Society score and clinical outcome. We observed no postoperative infection. One case of local recurrence was observed, and a hip dissection was performed. The Musculoskeletal Tumor Society score was 79.26 ± 1.26 (mean ± standard deviation) (range: 76‐80.3). Three patients remained disease-free, one survived but with disease, and one died of disease. Wrapping vancomycin-containing cement around the MP may be a useful method of preventing postoperative joint infections.